ANALISIS HUKUM KEDUDUKAN PENGGUNAAN CEK DAN BILYET GIRO SEBAGAI JAMINAN UTANG DALAM HUBUNGAN BISNIS - Julisman Julisman; Bismar Nasution; Mahmul Siregar; Mahmud Mulyadi (USU LAW JOURNAL, 2017)
ABSTRACT   Cheque and Bilyet Giro is a payment instrument that is recognized in payment payment system in Indonesia. Initially "cheque" are first known and used by the public as a means of payment is legitimate because the cheque by its nature is cash and portable payments. With cheque as a cash payment tool to replace cash, the public is very fond of using it until it eventually leads to a lot of empty cheque in business transactions. To regulate the cheque for not being misused, the Government of Indonesia issued Law No. 17 of 1964 concerning Prohibition of Withdrawal of Blank Cheque, which essentially prohibits the use of blank cheque as they may disrupt, disrupt, and frustrate government efforts in implementing stability improvements in monetary and economic sectors. According to Article 1, Article 2, and Article 3 of the provisions, the use of blank cheque may be subject to severe punishment, in the form of death penalty, life imprisonment and at least 20 (twenty) years imprisonment. Such provision causes the public no longer free to use the cheque and cause the Indonesian economy to deteriorate until finally the provision is revoked based on Government Regulation in Lieu of Law No. 1 Year 1971.   KeyWords : Use of cheque and bilyet giro; Means of payment; and Debt guarantees in business relationship.